Pancreatoblastoma : A case report - Indrawati, Indrawati Rahmayani, Susi Hariyati, Soeripto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
A 2.5 year old female child was admitted to Dr. Sardjito Hospital with complaint of enlargingÂ abdomen since 6 months. She was apparently well until 3 months prior to admission when she hadÂ anorexia and weight lost. Physical examination revealed a solid intrabdominal mass (15x13 cm) withÂ smooth surface and no tenderness. USG of the abdomen showed a large mass in paraaortal region andpushed the aorta. Operation was done and during exploration the mass was located as high as the stomachlevel and extended into the pancreas. Gross examination showed the tumor was 11x11x8 cm, encapsulated,nodular, white cut surface, some parts were brown and most of them were fragile. The diagnosis ofpancreoblastoma was established by immunohistochemical examination.Â The presenting features of pancreoblastoma are generally nonspecific and clinically difficult to distinguishfrom other intraabdominal tumors such as neuroblastoma, non-Hodgkin lymphoma, Wilms tumor,Â hepatoblastoma and desmoblastoma. Some clinical tests might suggest these tumors, i.e. multiorganÂ involvement for non-Hodgkin lymphoma; renal origin, the propensity for venous invasion and for thepulmonary metastasis for Wilms tumor. aÂfeto protein that is positive in either hepatoblastoma orÂ pancreoblastoma cannot differ both tumors. Another intrabdominal tumor that should be considered isÂ desmoblastoma that positive vimentin stain. The positive CAM5.2. as well as cytokeratin and the negativeÂ vimentin in immunohistochemical examination confirmed the diagnosis of pancreoblastoma.Keywords : pancreoblastoma Â child Â intraabdominal tumors Â immunohistochemical examination